Experimental investigation of flexural strength and plane strain fracture toughness of carbon/silk fabric epoxy hybrid composites - Madhavi Polepalli; Chandra Shekar Kaspa; Narender Gorentla; Harinatha Reddy Maddika; Jaya Prakash Kode; Varalakshmi Machireddy Venkata; Udaya Bhaskar Sape (Journal of the Mechanical Behavior of Materials)
Comparing polymer matrix composites with conventional composites, such as continuous fiber-reinforced composites, shows a considerable increase in strength and fracture toughness. In this study, compression molding was used to create hybrid (carbon and silk fabric-reinforced) and carbon fabric-reinforced epoxy matrix composites using a hand layup process. This article discusses the evaluated flexural strength (FS) and plane strain Mode-I fracture toughness of composite materials. The impact of carbon fabric reinforcement on the fracture toughness of these composites was assessed using the obtained results. It was found that the addition of silk fabric reinforcement decreased the hybrid composite’s plane strain Mode-I fracture toughness. Fracture toughness and FS are higher in carbon fabric-reinforced composite than in hybrid composite.